Oil-based or saline contrast for sono-hysterosalpingography in infertile women: a pilot randomized controlled double blind trial - Richard S. Legro, M.D; Christy M. Stetter, B.S; Allen R. Kunselman, M.A; William M. Geisler, M.D., M.P.H; William C. Dodson, M.D; Stephanie J. Estes, M.D (Elsevier, 2023)
Objective: To determine the feasibility, safety, and outcomes of an oil-based, iodinated contrast using office-based, ultrasound-imaged hysterosalpingography in women with infertility. Design: Randomized Controlled Double Blind Clinical Trial. Setting: Academic health center. Intervention(s): Tubal flushing with oil-based contrast medium (Lipiodol UF) versus saline. Main Outcome Measure(s): Ongoing pregnancy rate, pain, quality of life, and thyroid function. Result(s): Forty-eight patients (24 in each group) were analyzed. The groups were well-matched at baseline. Ongoing pregnancy was noted in 17% (4/24) of the oil-contrast group versus 37% (9/24) in the saline group. Saline group patients more frequently initiated infertility therapy in the six-month follow-up period (saline, 67% vs. oil, 33%), and no serious adverse events in either group. There were no differences in pain from the procedure between groups. There were no differences in thyroid function tests postprocedure between groups, but within the oil-contrast group, there was a slight increase in thyroid-stimulating hormone (post vs. preratio of geometric means: 1.18; 95% confidence interval [CI], 1.02-1.38) and decrease in Free T4 (postdifference vs. predifference in means: 0.08 ng/dL; 95% CI, -0.14 to -0.01). Immediately after the test, the physicians correctly guessed 79% of oil and 71% of saline randomization assignments, whereas patients correctly guessed 63% of oil and 38% of saline. Conclusion(s): This pilot study demonstrates the safety and feasibility of giving an oil-based contrast medium during ultrasound-imaged hysterosalpingography. Pregnancies were seen after oil-based administration, and this contrast is associated with minor thyroid function impairment.